On the experimental evaluation of the permeability in porous media using a gas flow method - Miguel, A. F. (2012)
Several studies indicate that experimental determination of porous medium permeability by a gas ﬂow method may be inﬂuenced by gas properties and ambient temperature. In order to explain these inﬂuences, a very simple model is developed based on the idea that the ﬂow in the porous medium may results from both pressure-driven and free molecular ﬂows. Measurements of the permeability of sand and a woven ﬁbrous material performed with air and helium ﬂows seem to corroborate this view. Based on the approach developed, we also study the phenomenon known as slip, and a methodology to quantify the slip length is presented.